45 Years of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Challenges for Global Governance Regarding Gender Inequality - Tainah Sales; Felipe Cavaliere Tavares (Pensar, 2025)
History confirms that there have always been women who resisted the effects of patriarchy; however, feminist movements gained greater strength and formal adherence by States especially from the 1970s onward. From the perspective of global initiatives, the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) stands out—a 1979 treaty that is part of the universal human rights system. Nevertheless, despite this initiative and others that followed, the context of violence, male domination, and the invisibility of women in public spheres of power persists. Thus, the question arises: What causes the patriarchal structure to remain strong worldwide 45 years after the advent of CEDAW and 76 years after the Universal Declaration of Human Rights? This is the central issue the article seeks to address, through an analysis of the international patriarchal context in light of cosmopolitan feminism. This model rejects the Eurocentric, liberal, and falsely universalized imposition regarding the understanding of human rights, proposing instead their reinterpretation from a perspective that considers cultural differences among peoples and the role of multi-level governance in a globalized world. Structural changes are necessary, involving both state and non-state actors, as there is still, in general, an invisibility of this agenda within cosmopolitan political discourse. The article seeks to discuss the hierarchy that structures international politics and prevents the feminist struggle from advancing and producing more concrete effects.